Non-invasive monitoring of stress biomarkers in the newborn period. Issue 4 (August 2019) - Peña-Bautista, C.; Escrig, R.; Lara, I.; García-Blanco, A.; Cháfer-Pericás, C.; Vento, M.
Abstract: The neonatal period is a highly sensitive time span during which stressful experiences may have an influence on later health outcomes. Medical procedures applied to newborn babies during hospitalization are stressors that trigger a physiological and psychological stress response. Stress response has been traditionally evaluated using scores based on behavioural signs such as facial expressions, limb movements, crying, etc., which are subjectively interpreted. Only few studies have employed measurable physiological signs to objectively evaluate the stress response to specific interventions. The aim of this review is to inform of recently developed biochemical methods that allow clinicians to evaluate the stress response to medical procedures performed in the neonatal period in biological samples non-invasively obtained. Stress biomarkers are based on the physiological stress response mediated by the hypophysis-pituitary-adrenal axis and the sympathetic-adreno-medullary systems. Cortisol is at present the most widely employed laboratory determination to measure stress levels. In recent years, sequentially determined salivary cortisol levels have allowed non-invasive monitoring of newborn infants under stressful conditions in the NICU.